Cerebellar vasculitis due to systemic lupus erythematosus and suboccipital decompression: case report - Castro-Castillo, Elder (2024)
Arterial vasculitis or cerebellar vasculitis in systemic lupus erythematosus (SLE) are extremely infrequent, and these might be included within cases of neuropsychiatric SLE (NPSLE), cerebellar stroke in SLE, and within the group of central nervous system vasculitis due to SLE. The addition of surgical management to this condition has been reported in few publications. We present the case of a 18- year old female patient with SLE, NPSLE, and cerebellar stroke, highly suspicious of inflammatory vasculitis affecting cerebellar arteries, in whom, in spite of medical management, suboccipital decompression was performed. Inflammatory vasculitis of cerebellar arteries in SLE is an infrequent cause of cerebellar stroke, and it has elevated mortality rates. There is limited scientific evidence with respect to suboccipital decompression for the management of this condition.